Development of a PZT device-based power-generating shoes for disaster-affected areas. (March 2020) - Tsukagoshi, S; Seto, K; Hashimoto, S; Basari, A A
Abstract: A PZT device is an element that generates electric power when an impact is applied by vibration. Currently, PZT devices are installed on the floor near the ticket gates to supply power to station equipment, and on the floor of bridges to turn on LEDs at night. Since the current generated by the PZT device is small, there is a disadvantage that the electric power obtained is small. In this paper, we developed a power-generating shoe using PZT devices for use in disaster-affected areas where power shortages tend to occur. The validity of the developed power-generating shoes is experimentally evaluated under the variation of PZT device, shoes and secondary batteries. At present, the result is that it is possible to charge about 1.5% of mobile phones at the maximum. In order to reduce loss and obtain more power, it is necessary to improve shoes and to build a charge / discharge circuit.